Downstreaming of vacuum frying technology and quality standardization: Accelerating the competitiveness of horticultural products in the Sumberberas Farmers Group - Susilo, Bambang; Suhartini, Sri; Oktavianty, Okke; Perianti, Desi Dewi; Kette, Arlindo Umbu Saki; Rohim, Abd.; Azra, Wafa Nida Faida; Samudra, Rizki Putra; Islamiya, S.; Anarizkia, Vian Medika; Wahyudi, Andreas Farhan; Kiswahati, Arum; Tsabita, Az Zahra Amalia; Lukas, Maria Angeline Viola; Sipayung, Ferdy Mandes; Rafi, Muhammad Rezaul (Community Empowerment, 2026)
Sumberkencono Village possesses significant horticultural potential, yet post-harvest limitations hinder its economic optimization. This program aims to empower the Sumberberas Farmer Group through the integration of vacuum frying technology, quality standardization (GMP), and business legality (NIB and P-IRT). The methodology followed a participatory technology transfer approach, including intensive production mentoring and digital marketing optimization. Results demonstrated a significant improvement in product quality, characterized by better texture and oil-content stability, alongside the successful formalization of business legality. The integration of Shopee and TikTok Shop as marketing channels further expanded the group's reach into the digital retail landscape. This initiative proves that the synergy between post-harvest engineering and administrative compliance is crucial for transforming traditional farmer groups into competitive agro-industrial units.